2019
DOI: 10.1101/2019.12.18.881573
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Water lily (Nymphaea thermarum) draft genome reveals variable genomic signatures of ancient vascular cambium losses

Abstract: For more than 225 million years, all seed plants were woody trees, shrubs, or vines (1)(2)(3)(4). Shortly after the origin of angiosperms ~135 million years ago (MYA) (5), the Nymphaeales (water lilies) became one of the first lineages to deviate from their ancestral, woody habit by losing the vascular cambium (6), the meristematic population of cells that produces secondary xylem (wood) and phloem. Many of the genes and gene families that regulate differentiation of secondary tissues also regulate the differe… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 97 publications
0
2
0
Order By: Relevance
“…The evolutionary relationships among the plants in the NFC are unclear, and no consensus on an evolutionary tree has been obtained in previous studies (Griesmann et al ., 2018; One Thousand Plant Transcriptomes, 2019; Povilus et al ., 2020; Y. Yang et al. , 2020), which is possibly because different gene sets were used to construct the species phylogeny.…”
Section: Resultsmentioning
confidence: 99%
“…The evolutionary relationships among the plants in the NFC are unclear, and no consensus on an evolutionary tree has been obtained in previous studies (Griesmann et al ., 2018; One Thousand Plant Transcriptomes, 2019; Povilus et al ., 2020; Y. Yang et al. , 2020), which is possibly because different gene sets were used to construct the species phylogeny.…”
Section: Resultsmentioning
confidence: 99%
“…The viviparous plantlets become mature in 20-30 days if cultivated in controlled conditions [6]. Recently, some studies on whole genome sequencing of water lilies have been reported [7,8]. Over the past few years, application of plant molecular biotechnological tools such as pollen-tube transgenics led to a lot of achievements in improving cold stress resistance and other traits in water lilies [9].…”
Section: Introductionmentioning
confidence: 99%